1994
DOI: 10.1111/j.1469-8749.1994.tb11856.x
|View full text |Cite
|
Sign up to set email alerts
|

Autism in Thalidomide Embryopathy: A Population Study

Abstract: SUMMARY Of a population of 100 Swedish thalidomide embryopathy cases, at least four met full criteria for DSM‐III‐R autistic disorder and ICD‐10 childhood autism. Thalidomide embryopathy of the kind encountered in these cases affects fetal development early in pregnancy, probably on days 20 to 24 after conception. It is argued that the possible association of thalidomide embryopathy with autism may shed some light on the issue of which neural circuitries may be involved in autism pathogenesis. RÉSUMÉ Autisme d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
162
0
7

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(169 citation statements)
references
References 11 publications
0
162
0
7
Order By: Relevance
“…As noted previously, autism risk factors include environmental challenges, such as maternal use of pharmaceutical agents with neurotoxic effects, [226][227][228]241,242 prenatal exposure to viral infections or maternal stress 233,234 and, in addition, exposure to high levels of environmental pollutants, including heavy metals. 275,276 A recent review by Herbert et al 7 identified 135 genes that have been shown to mediate responses to environmental challenge, and that are located within autism linkage regions.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…As noted previously, autism risk factors include environmental challenges, such as maternal use of pharmaceutical agents with neurotoxic effects, [226][227][228]241,242 prenatal exposure to viral infections or maternal stress 233,234 and, in addition, exposure to high levels of environmental pollutants, including heavy metals. 275,276 A recent review by Herbert et al 7 identified 135 genes that have been shown to mediate responses to environmental challenge, and that are located within autism linkage regions.…”
Section: Genes Responsive To Environmental Factorsmentioning
confidence: 97%
“…[235][236][237] These physical manifestations are predictive of greater symptom severity and neuroanatomical abnormalities. 235,238,239 Exposure to teratogens during gestation has also been shown to be a risk factor for autism, with higher disease incidence associated with maternal use of valproic acid, [226][227][228]240 thalidomide 241 and misoprostol. 242 The detrimental neurodevelopmental effects of maternal infection have been attributed, in part, to the induction of inflammatory cytokines.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…These agents could directly damage the mitochondria and reduce their efficiency, or impair functional activity by increasing body burden of free radicals and resultant oxidative stress. Drugs like valproic acid and thalidomide [68,69] , as well as exposure to viruses such as rubella and cytomegalovirus [70,71] are examples of environmental factors that have a known causal role in autism. However, many more environmental toxins including pesticides [53,72] , polychlorinated biphenyls (PCB's) [73] , industrial chemicals [73][74][75][76] , and toxic metals such as mercury [77,78] , lead [79,80] , cadmium, nickel [74] , and tin [81] have also been implicated in ASD.…”
Section: Possible Causes Of Mtd In Autismmentioning
confidence: 99%
“…In Japan, the prevalence of autistic disorders has been reported to be 3 times higher in children hospitalized in neonatal care units than in the general population [28]. In some cases, autism is associated with insults early in gestation, including thalidomide embryopathy in 4% to 5% of cases, probably due to damage to the CNS in the early stages of gestation [29]. Autism occasionally occurs as a result of maternal ingestion of anticonvulsants [30].…”
Section: Pre-and Perinatal Factorsmentioning
confidence: 99%